Understanding the Basics of AI Driven Cloud Services - Prathmesh Balsurkar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Artificial Intelligence (AI) has transformed cloud computing into smarter, automated, and more efficient systems. AI-driven cloud services leverage machine learning, natural language processing, and predictive analytics to optimize resource allocation, enhance security, and streamline data management. These intelligent services improve scalability, reduce operational costs, and increase computational efficiency across industries. This paper presents the fundamental concepts of AI-driven cloud services, highlighting their key components, benefits, and real-world applications. It explores how AI enhances cloud operations through automated monitoring, self-healing infrastructures, and intelligent decision-making. The study also examines AI’s role in cloud security, data analytics, and personalized user experiences. Major providers such as Amazon Web Services (AWS), Microsoft Azure, and Google Cloud integrate AI tools for automated insights, fraud detection, and predictive maintenance. Despite its advantages, AI-based cloud computing faces challenges like data privacy, ethical concerns, and high computational demands. Addressing these through strong governance and innovative architectures can shape the future of AI-driven cloud ecosystems.
Keywords: Artificial Intelligence (AI); Cloud Computing; Machine Learning; Automation; Cloud Security; Digital Transformation